Determinants of Enterprise Risk Management Implementation: An Empirical Analysis of Commercial Banks in China - Wang, Bingying (2020)
After the financial crisis, more and more companies realize that enterprise risk management (ERM), as a necessary tool, can help them survive in the fluctuating financial market. Although companies have developed ERM, they still have insufficient understanding of the successful ERM implementation factors. Most research is based on European and American countries, but there are few studies on developing countries such as China. Therefore, this article mainly studies the implementation of ERM and its factors in Chinese commercial banks during the period from 2010 to 2019. The study collect financial data and public information through database and annual reports. STATA16 is applied to panel data regression. From empirical results, they show that larger bank size and higher the return on assets (ROA) like state-owned banks have a strong influence on the implementation of ERM, while a positive relationship between the high financial leverage and ERM implementation such as joint-stock banks and urban banks. This research provides preliminary information on the situation of ERM in China’s banking sector. In addition, these findings are helpful to improve the role of the board of directors and strengthen regulatory policies. Therefore, this article recommends further research on the determinants of the ERM system, especially investigations of commercial banks with different properties.